Rancang Bangun Alat Pemilah Ikan Berbasis Internet Of Things (IoT) - Mochamad Andri Prassetyo; Henna Nurdiansari; Kuntoro Bayu Ajie (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Mochamad Andri Prassetyo, Design of Fish Sorter Equipment Based on INTERNET of THINGS (IoT). Supervised by Henna Nurdiansari, S.T., MT., M.Sc. and Kuntoro Bayu Ajie, S.Kom., MT. According to data compiled by the Ministry of Maritime Affairs and Fisheries, the amount of fish produced by Indonesian seas has reached 12.01 million tonnes in 2022. The enormous potential of Indonesian marine products forces the need for technological intervention to help reduce production costs. Improving the quality of the products produced. One of the processes that requires technological intervention is the process of sorter fish that have been caught by fishing vessels and then having to be regrouped according to the weight of the fish. By adopting sophisticated technology and systems in the modern fisheries market, efforts to achieve efficiency and reduce the risk of human error can be increased. Internet of Things (IoT) is a technological concept that has the ability to connect and facilitate the communication process between machines, devices, sensors and humans via the internet network. After conducting Research and Development (R&D), designing an Internet of Things-based fish sorting tool could become a new technology that can increase product efficiency by designing a system, designing tools and testing plans for sorting fish based on measuring the weight of the fish. Based on the test results, it can be concluded that the design of an Internet of Things-based fish sorting tool can detect fish entering the container that has been prepared through component testing and after testing the entire tool, data on the results of weight measurements on fish using the fish sorting system can be sent to Google Spreadsheet. So that the data can be accessed publicly by sending a predetermined link.